Dragons and lizards - Barrett, Norman S. frey50 (Franklin Watts New York, 1991)
A look at the feeding habits, reproductive behavior, and other life functions of lizards living in desert, tropical, and temperate environments.
Includes index
Keywords: Lizards -- Juvenile literature